2021
DOI: 10.3847/1538-4357/ac1b9c
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Photospheric and Chromospheric Magnetic Field Structures Associated with Chromospheric Heating over a Solar Plage Region

Abstract: In order to investigate the relation between magnetic structures and the signatures of heating in plage regions, we observed a plage region with the He i 1083.0 nm and Si i 1082.7 nm lines on 2018 October 3 using the integral field unit mode of the GREGOR Infrared Spectrograph (GRIS) installed at the GREGOR telescope. During the GRIS observation, the Interface Region Imaging Spectrograph obtained spectra of the ultraviolet Mg ii doublet emitted from the same region. In the periphery of the plage region, within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 141 publications
3
21
2
Order By: Relevance
“…Our results are somewhat different than those reported by Anan et al (2021), but surprisingly also compatible. Their observations were based on arguably lower spatial-resolution slitspectrograph raster scans in the Mg ii h&k lines (IRIS) and in the He i 10830 Å line.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our results are somewhat different than those reported by Anan et al (2021), but surprisingly also compatible. Their observations were based on arguably lower spatial-resolution slitspectrograph raster scans in the Mg ii h&k lines (IRIS) and in the He i 10830 Å line.…”
Section: Discussioncontrasting
confidence: 95%
“…The exact set of processes that are at work in plage and their contribution to the energy budget remains highly unconstrained from observations. A great discussion and exhaustive review about the potential contribution of different heating mechanisms in plage is presented by Anan et al (2021). They also analyzed the correlations of the radiative flux in the Mg ii h&k lines and with the magnetic field strength that was inferred from observations in the He i 10830 Å line.…”
Section: Introductionmentioning
confidence: 99%
“…Although we have been concerned here only with the heating of the corona, it may be that mixed-polarity flux on even smaller scales plays an important part in chromospheric heating, given the power law distribution of flux emergence. In their high-resolution spectropolarimetric study of chromospheric heating in a plage region, Anan et al (2021) found that the Mg II radiative flux (a measure of the heating rate) was highest in between or at the edges of the individual strong field patches within the plage, and was poorly correlated with the local chromospheric or photospheric field strength. Reconnection with small bipoles scattered through the plage might account for such off-center heating.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Similarly, Aschwanden et al (2007) mentioned as a "caveat" against the chromospheric evaporation scenario "the nondetection of the initial heating agent (small-scale reconnection events in the transition region)". More recently, in their observational study of the relation between magnetic structures and signatures of heating in a plage region, Anan et al (2021) found that the fraction of opposite-polarity fields was too small to support reconnection mechanisms, except possibly in the "strong guide-field regime." However, we have recently come to question the reliability of present-day magnetograms in detecting minority-polarity flux in the presence of a strongly dominant polarity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation